Social, Cultural, and Political Studies of the Legendary Resistance of Ukrainians During Russia’s War on Ukraine - Oksana Koshulko (Britain International for Academic Research (BIAR-Publisher), 2023)
The article is dedicated to exploring social, cultural, and political studies of the legendary resistance of Ukrainians, Crimean Tatars, and other multicultural and multinational minorities of the state during Russia’s part- and full-scale invasion of Ukraine, to discussing many significant topics of political and social prerequisites on the way to Ukrainian victory, starting from the glorious history of Kyivan Rus in the X-XI century; the character of ecocide and genocide during Russia’s part- and a full-scale invasion of Ukraine of 2014-24-, post-traumatic stress of the Ukrainian nation because of the war during the last ten years of the war 2014-24; the situation about the Ukrainian heroes and traitors in Ukraine, explanation about Russian dissidents, ‘Foreign Agents,’ and traitors of Ukrainian origin in Russia; the situation how Ukraine became the focus of Western culture and arts.